The impact of efficiency and market structure on the financial performance: empirical evidence from China’s banking sector - Xu , Honghai; Liu, Qi (Transformations In Business & Economics, 2025)
Against the backdrop of structure-conduct-performance (SCP) and efficient-structure (ESH) hypotheses, this research investigates the impact of the market structure on the performance of banks in China from 2015 to 2024. The DEA method is adopted to gauge the efficiency of banks, whereas the concentration ratio is utilised to evaluate the market structure of Chinese banks. Using random regression analysis, both variables (market structure and efficiency of banks) among other independent variables (market share, loan ratio, bank size, and operating expenses) are regressed upon the explained variable, namely the financial performance of Chinese banks represented by ROA. In this study, a trend analysis is also carried out to analyse the performance of the Chinese banking sector. The regression results show that both the market structure and the efficiency of banks exert a noticeable positive influence on the banks’ performance in China, supporting the ESH and rejecting the SCP hypothesis. This implies that banking efficiency and market structure (concentration) significantly affect the profitability performance of Chinese commercial banks. From the structural perspective, the concentration of Chinese banks is on a declining trend, and the Chinese banks are more competitive due to less concentration of the market. In the context of efficiency, DEA analysis shows that banks in China are operating below their efficient capacity. Thus, Chinese banks could lessen the utilisation of their inputs to operate in an efficient manner.